(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the situations that future history teachers may encounter in the process of studying history in the current era of global information. It concludes that students must be the organizers and active participants in understanding history, regardless of the circumstances. This requires recognizing human abilities, intellect, intellectual capabilities, and human values in general, which can only be formed on a well-founded basis for developing viewpoints and providing an objective assessment. Furthermore, it is revealed that historical processes can only genuinely express their humanitarian essence and universal values through human beings.